Veritas graeca, veritas latina et veritas confessionis w staropolskich tłumaczeniach Nowego Testamentu na przykładzie Listu Jakuba - Wojciechowska, Kalina; Rosik, Mariusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article aims at the example of the Letter of James to show how the theological reforms and hermeneutic and critical New Testament editions were reproduced in Polish translations of the 16th and 17th centuries. The authors show that on the level of textual criticism and philological solutions, Polish New Testament translators really derived from the achievements of European biblical studies, but remained faithful to the confessional tradition and not to the Greek testimonies. The reception of Reformation at the hermeneutic and theological level looks much worse. Interpreters usually do not take up polemics or defensive positions.